2009
DOI: 10.1002/ar.20991
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Bone Tissues in a Turkey Vulture and a Nonavian Dinosaur: Implications for Interpreting Endosteal Bone and Radial Fibrolamellar Bone in Fossil Dinosaurs

Abstract: We report on similar pathological bone microstructure in an extant turkey vulture (Cathartes aura) and a nonavian dinosaur from Transylvania. Both these individuals exhibit distinctive periosteal reactive bone deposition accompanied by endosteal bone deposits in the medullary cavity. Our findings have direct implications on the two novel bone tissues recently described among nonavian dinosaurs, radial fibrolamellar bone tissue and medullary bone tissue. On the basis of the observed morphology of the periosteal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 37 publications
3
77
0
Order By: Relevance
“…Sharpey's fibers are also embedded within the irregular tissue patch, thus appearing to be continuous with those in the surrounding parallel‐fibered bone. This layer of woven fibered bone resembles the pathological, reactive bone tissue observed in other archosaurs (Reid, ; Chinsamy and Tumarkin‐Deratzian, ).…”
Section: Resultssupporting
confidence: 62%
“…Sharpey's fibers are also embedded within the irregular tissue patch, thus appearing to be continuous with those in the surrounding parallel‐fibered bone. This layer of woven fibered bone resembles the pathological, reactive bone tissue observed in other archosaurs (Reid, ; Chinsamy and Tumarkin‐Deratzian, ).…”
Section: Resultssupporting
confidence: 62%
“…) showing a regional change to reticular FLB. Furthermore, close to the peripheral edge, there is a thin band of radially oriented FLB which resembles the sunburst pattern typical of periosteal reactive growth (Chinsamy and Tumarkin‐Deratzian, ). A similar band of radial FLB is also present in tibia NMQR 1705/561.…”
Section: Discussionmentioning
confidence: 93%
“…This well vascularized, endosteally formed tissue characteristically has a cancellous or spongy texture and consists of woven bone [9][10][11][12][13] . Endosteal deposits are sometimes caused by disease (for example, avian osteopetrosis) and in such cases they are usually accompanied by bony periosteal outgrowths 13 . In DNHM-D1874, the periosteal surface of the humerus (and other bones in the skeleton) does not have any reactive deposits, which supports our conclusion that the endosteally derived tissue is not pathologic in origin.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that the deposition of avian medullary bone is directly linked to the maturation of the ovarian follicles before egg laying, and that it acts as a calcium reservoir for the production of the calcareous eggshell [9][10][11][12][13][14][15] . The deposition of medullary bone is considered to be an adaptation to compensate for the thin-walled bones of birds, from which extensive bone resorption leads to brittleness and susceptibility to fractures 11,14,15 .…”
Section: Resultsmentioning
confidence: 99%